2020
DOI: 10.7759/cureus.11058
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Cannabis Use and Risk of Prescription Opioid Overdose: Insights from Pediatric Inpatients

Abstract: Our first goal is to evaluate the prevalence of hospital admissions for prescription opioid overdose (POD) in pediatric inpatients, and next goal is to measure the independent association between cannabis use disorders (CUD) and POD. Methods We used the nationwide inpatient sample (NIS) and included 27,444,239 pediatric inpatients (age ≤ 18 years), and 10,562 (0.04%) were managed primarily for POD. The odds ratio (OR) of the association of variables in POD inpatients was measured using the binomial logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…Our study found that POD hospitalizations were prevalent in females (54.1%), elders in the 51-75-year age group (48.5%), whites (81.5%), and those in the lower household income quartet (32.8%). Past studies reflect our results where whites (67%) and those from low-income families had a higher likelihood for POD-related hospitalization [16]. Opioid prescription is more prevalent among whites because there is an unconscious bias resulting in under-prescription towards racial/ethnic minorities.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our study found that POD hospitalizations were prevalent in females (54.1%), elders in the 51-75-year age group (48.5%), whites (81.5%), and those in the lower household income quartet (32.8%). Past studies reflect our results where whites (67%) and those from low-income families had a higher likelihood for POD-related hospitalization [16]. Opioid prescription is more prevalent among whites because there is an unconscious bias resulting in under-prescription towards racial/ethnic minorities.…”
Section: Discussionsupporting
confidence: 84%
“…Since 2005, opioid-related hospitalizations have increased dramatically [4]. Past studies have shown a higher odds of association with POD-related hospitalizations in pediatric inpatients with comorbid SUD [16]. A past study found that overdose among children correlated to accidental or unintentional overdose from parental opioid prescriptions [20].…”
Section: Discussionmentioning
confidence: 99%
“…Microglial inflammatory activation has been reported to induce cognitive impairment ( Feng et al, 2017 ; Zhao et al, 2019 ). Cognitive impairment in POD is associated with anxiety, memory impairment and other symptoms ( Gao X. et al, 2020 ; Pankaj et al, 2020 ; Ren et al, 2021 ). Therefore, according to our above findings in this study, we wanted to determine whether ATP supplementation can alleviate cognitive impairment to a certain extent.…”
Section: Resultsmentioning
confidence: 99%